Ion motion in crossed fields and separation mechanism in “Archimedes Plasma Mass Filter” - Yeliseyev, Yu.N. (Вопросы атомной науки и техники, 2016)
Trajectories of ions produced due to ionization of neutral particles (atoms, molecules) by electron impact in
plasma are determined. The plasma is placed in crossed fields with positive radial electric field. It is shown that the
light ions produced at the plasma periphery leave the plasma volume. Therefore, in the ‘Archimedes Plasma Mass
Filter’ device, not only heavy but also light ions can hit a radial collector, what have to reduce essentially the degree
of separation of light and heavy components of nuclear waste. The dependence of currents of light and heavy ions
along radius (to the radial collector) and along device axis (to the end collector) are calculated. The conclusion is
made about impossibility of complete separation of light and heavy components of nuclear waste in their single pass
through the ‘Archimedes Plasma Mass Filter’ device. Определены траектории ионов, которые образовались в результате ионизации нейтралей (атомов, моле-
кул) электронным ударом в плазме в скрещённых полях при положительном радиальном электрическом
поле. Показано, что в таком поле лёгкие ионы, образовавшиеся на периферии плазмы, выходят за её преде-
лы. В “Archimedes Plasma Mass Filter” это должно приводить к попаданию на радиальный коллектор не
только тяжёлых, но и лёгких ионов, что существенно снизит степень разделения лёгкой и тяжёлой компо-
нентов отходов ядерного производства. Рассчитаны потоки лёгких и тяжёлых ионов по радиусу (на ради-
альный коллектор) и вдоль оси устройства (на торцевой коллектор). Сделан вывод о невозможности полного
разделения лёгкого и тяжёлого компонентов отходов в “Archimedes Plasma Mass Filter” за один проход. Визначені траєкторії іонів, які утворилися в результаті іонізації нейтралей (атомів, молекул) електронним
ударом у плазмі в схрещених полях при позитивному радіальному електричному полі. Показане, що в тако-
му полі легкі іони, що утворилися на периферії плазми, виходять за її межі. У “Archimedes Plasma Mass
Filter” це повинне приводити до влучення на радіальний колектор не тільки важких, але й легких іонів, що
суттєво знизить ступінь поділу легкої й важкої компонентів відходів ядерного виробництва. Розраховані
потоки легких і важких іонів по радіусу (на радіальний колектор) і уздовж осі пристрою (на торцевий колек-
тор). Зроблений висновок про неможливість повного поділу легкої та важкої компонентів відходів в
“Archimedes Plasma Mass Filter” за один прохід